A nitrogen-doped graphene-supported nickel-single-atom catalyst in the flow cell meets the industrial criteria of carbon dioxide reduction reaction to carbon monoxide - Lu, Yi-Hsuan; Tsai, Hsin-Jung; Huang, Wen-Yang; Lee, Tsung-Ju; Lin, Zih-Yi; Hsu, Shao-Hui; Hung, Sung-Fu (Frontiers in Catalysis, 2022)
Carbon dioxide reduction reaction (CO2RR) is a promising approach to accomplishing net zero CO2 emissions. Among CO2RR catalysts, nitrogen-doped graphene-supported single-atom catalysts show a remarkable conversion rate from CO2 to CO; however, the low production amount has been limited using the conversion H cell, hindering its industrial development. In this work, we synthesize a nitrogen-doped graphene-supported nickel-single-atom catalyst and conduct CO2RR in a flow cell, exhibiting a CO2-to-CO Faradaic efficiency of 96% and a partial current density of 144 mA cm-2. It can also achieve the highest partial current density of 204 mA cm-2 with a turnover frequency of 7852 h-1. According to the techno-economic analysis, these preeminent activities meet the industrial criteria (Faradaic efficiency > 60% and partial current density > 100 mA cm-2). This activity enhancement using a flow system can significantly accelerate net-zero CO2 emission realization.